Socio-psychological aspects of religiosity (a case of Belarusian Tatar Muslims) - Karassyova, Svetlana G.; Reut, Lizaveta V. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
A working definition of religion is proposed, and its aspects such as experience, system, and tradition are differentiated. The dichotomy of the sacred (ritual) and profane (everyday) spheres of worldview and lifestyle of religion followers is characterised. It is determined that the symbolism of the boundary between the sacred and the profane signifies its conventionality and leads to the partial blurring of the canonical purity of religion on its periphery, where the profane dominates, while maintaining the canon on the axis of its transmission, where the sacred is protected. The mission of those followers of the religion who specialise in the knowledge of the canon and the performance of rituals (priests) is outlined in relation to the erosion of the canon. It is stated that their tasks include a critical analysis of the para-, non-, and foreign-religious components that infiltrate the content of the religion on its periphery (at the level of everyday practices of ordinary followers) and the canonically acceptable integration of these components into the religious system.
Keywords: religion; religious identity; Belarusian Tatar Muslims; sacred and profane; syncretism; monotheistic traditions